2020
DOI: 10.1038/s41467-020-18287-x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of arterial macrophages defines their functions in homeostasis and inflammation

Abstract: Arterial macrophages have different developmental origins, but the association of macrophage ontogeny with their phenotypes and functions in adulthood is still unclear. Here, we combine macrophage fate-mapping analysis with single-cell RNA sequencing to establish their cellular identity during homeostasis, and in response to angiotensin-II (AngII)-induced arterial inflammation. Yolk sac erythro-myeloid progenitors (EMP) contribute substantially to adventitial macrophages and give rise to a defined cluster of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 70 publications
9
77
1
Order By: Relevance
“…Multiple processes determine macrophage accumulation in the plaque, including monocyte recruitment and differentiation, macrophage proliferation, death and egress [32]. Macrophages of prenatal origin reside in the adventitia and self-sustain through proliferation into adulthood largely independent of monocyte recruitment [15,65]. Whether these embryonically derived macrophages in the adventitia directly contribute to macrophages accumulating in intimal lesions is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple processes determine macrophage accumulation in the plaque, including monocyte recruitment and differentiation, macrophage proliferation, death and egress [32]. Macrophages of prenatal origin reside in the adventitia and self-sustain through proliferation into adulthood largely independent of monocyte recruitment [15,65]. Whether these embryonically derived macrophages in the adventitia directly contribute to macrophages accumulating in intimal lesions is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the expression profiles of eYFP-negative bone marrow-derived and eYFP-positive EMP-derived macrophages in the postnatal tissue of Rank-Cre; Rosa26eYFP mice showed that macrophages from eYFP-positive EMPs expressed high levels of Lyve-1, Stab1, and Gas6, which have been related to homeostatic and anti-inflammatory immune functions. On the other hand, eYFP-negative HSC-derived macrophages characterizes higher expression of Ccr2, which is a marker of HSCs-derived monocyte/macrophage ( Weinberger et al, 2020 ). Use of these markers may be useful in future research to understand the contributions of these populations in homeostasis, tissue repair, and pathology.…”
Section: Unique Expression Profiles Of Emps- and Hscs-derived Macrophmentioning
confidence: 99%
“…A very brief and simplistic overview of M1/M2 biology is represented in Figure 1. However, there is a considerable heterogeneity in macrophage phenotypes and several subtypes have been described such as M1, M2a, M2b, M2c, M2d, Mhem, Mox, M4 (37)(38)(39)(40). This over simplistic representation of M1 as proinflammatory and M2 as anti-inflammatory macrophages is considered here to recognize different functional states of these polarized phenotypes to assign pro-inflammatory and antiinflammatory role.…”
Section: Macrophage Polarization and Intracranial Aneurysmsmentioning
confidence: 99%
“…Taken together, there are multiple strategies at the level of inflammation and macrophage modulation that have translational potential in human disease. However, the heterogeneity and the complexity of macrophageal response should be cautiously considered in future studies aiming at characterizing the role of these main sentinel cells of ICAs inflammation ( 39 , 40 ). A recent study revealed that during Ang-II induced inflammation of the aorta, primarily adventitial macrophage population expanded due to the infiltration of the bone marrow derived macrophages, whereas the residential embryonic macrophages do show local proliferation, but retain their homeostatic roles ( 40 ).…”
Section: Macrophage Modulation As a Treatment Strategy For Intracranimentioning
confidence: 99%
See 1 more Smart Citation